A Rare presentation of Takayasu Arteritis in Sub-Saharan Africa: A case report in a young female from Mauritius - Mooroogiah, Krissheeven; Banerjee, Indrajit; Maheshwara, Ramanah; Nunkoo , Sarvesh; Robinson, Jared; Banerjee, Indraneel (Journal of Biomedical Sciences, 2025)
Background: Takayasu’s arteritis (TKA) is a severe inflammatory form of large vessel vasculitis that primarily affects the aorta and its major branches. TKA is a rare disease, with a reported worldwide incidence rate of only 1 to 2 cases per million. Case presentation: This is a case report from Mauritius of a female 33 years in age suffering from TKA. Individuals with TKA exhibit infiltration of inflammatory cells into large vessels, resulting in the release of proinflammatory cytokines, including IFN-γ, TNF-α, IL-6, IL-8, IL-17A and IL-18. Both the clinical assessment and laboratory assessment of TKA are challenging. This instance serves as a poignant reminder of the potential severity and complexity of TKA. Conclusion: This report highlights and sheds light on the intricate process of diagnosing and managing TKA, accentuating the importance of thorough clinical assessments and meticulous history taking. By diving deep into the patient’s medical background, signs and symptoms as well as with the proper investigations, healthcare providers can swiftly recognize the distinctive features of TKA. This report also highlights the long-term follow-up for disease progression and the efficacy of treatment for patients diagnosed with TKA.